THE MAINTENANCE OF PLASMINOGEN ACTIVATOR INHIBITOR-1 IN BLOOD SERUM IN PATIENTS WITH TYPE 2 DIABETES MELLITUS - Kravchun, N.A. (The Journal of V. N. Karazin Kharkiv National University, series "Medicine", 1970)
The maintenance of plasminogen activator inhibitor-1 (PAI-1) in blood serum in patients with type 2 diabetes mellitus of the senior age group with long term of disease and the role of this index in the development of cardiovascular complications were studied. The statistically significant dependence of PAI-1 on arterial hypertension, fibrinogen, triglycerides, very low density lipoproteides, body weight index and insulin resistance was determined.It was shown, that PAI-1 was a significant additional risk factor in the development of cardiovascular diseases in patients with type 2 diabetes mellitus.